LANGUAGE USED BY ENGLISH TEACHERS IN A BILINGUAL SCHOOL IN INDONESIA - Antini, Ni Komang Ayu; Putu Artini, Luh; Nyoman Padmadewi, Ni (JURNAL KONFIKS, 2025)
This study aims to describe how English teachers use language in the learning process in bilingual schools and explore students’ opinions on this use. This study was conducted in a private elementary school that implements a bilingual education maintenance model, with third-grade students who were not exposed to English at home. Data were collected through participant observation and semi-structured interviews, then analyzed using thematic analysis based on Gallagher (2015) theory. The results show that teachers use English as the primary language of instruction, but provide clarification in Indonesian to ensure student understanding. Interviews revealed that students feel helped by the use of bilingualism, especially in understanding the material, remembering vocabulary, and building language confidence. These findings suggest that bilingual teaching strategies can improve the quality of English learning at the elementary level.